Correlates of androgens in wild male Barbary macaques: Testing the challenge hypothesis. Issue 10 (17th August 2017) - Rincon, Alan V.; Maréchal, Laëtitia; Semple, Stuart; Majolo, Bonaventura; MacLarnon, Ann
Abstract : Investigating causes and consequences of variation in hormonal expression is a key focus in behavioral ecology. Many studies have explored patterns of secretion of the androgen testosterone in male vertebrates, using the challenge hypothesis (Wingfield, Hegner, Dufty, & Ball, 1990; The American Naturalist, 136(6), 829–846) as a theoretical framework. Rather than the classic association of testosterone with male sexual behavior, this hypothesis predicts that high levels of testosterone are associated with male–male reproductive competition but also inhibit paternal care. The hypothesis was originally developed for birds, and subsequently tested in other vertebrate taxa, including primates. Such studies have explored the link between testosterone and reproductive aggression as well as other measures of mating competition, or between testosterone and aspects of male behavior related to the presence of infants. Very few studies have simultaneously investigated the links between testosterone and male aggression, other aspects of mating competition and infant‐related behavior. We tested predictions derived from the challenge hypothesis in wild male Barbary macaques ( Macaca sylvanus ), a species with marked breeding seasonality and high levels of male‐infant affiliation, providing a powerful test of this theoretical framework. Over 11 months, 251 hr of behavioral observations and 296 fecal samples were collected from seven adult males in the Middle Atlas Mountains, Morocco. Fecal androgen levels rose before the onset of the mating season, during a period of rank instability, and were positively related to group mating activity across the mating season. Androgen levels were unrelated to rates of male–male aggression in any period, but higher ranked males had higher levels in both the mating season and in the period of rank instability. Lower androgen levels were associated with increased rates of male‐infant grooming during the mating and unstable periods. Our results generally support the challenge hypothesis and highlight the importance of considering individual species' behavioral ecology when testing this framework. Abstract : Androgen levels peaked at start of the mating season. Androgens positively related to mating competition and negatively related to male‐infant grooming during the mating season. Androgen levels higher in dominant males during rank instability.